Tetrapods of sambaquis: biodiversity, culture, and conservation zooarchaeology - Mendes, Augusto Barros (2023)
Sambaquis are shell mounds common in the South and Southeast regions of Brazil. These archaeological sites were built by fishermen-gatherer-hunters who had an extreme affinity with marine and coastal environments, where they explored a great variety of fish and molluscs. Other groups of animals from these sites such as mammals, birds, reptiles, and amphibians are relatively less studied; thus, the objectives of this research are to bridge this information gap by identifying and inventoring the tetrapod fauna in sambaquis, understanding human-tetrapod interactions (cultural aspects such as hunting and capture, diet, and artifact manufacturing), and discussing how prehistoric biodiversity data can contribute to species conservation and management. Tetrapod remains from ten sambaquis of the South region of Brazil were anatomically and taxonomically identified and analysed regarding their use in diet and artifact manufacturing. We quantified data using NISP and MNI and estimated the intake of consumable meat (biomass) of the identified taxa. A total of 46 taxa were identified. As expected, most of the remains were from marine animals: Cetacea (NISP = 1,696), Mysticeti (NISP = 811, MNI = 8), and Otariidae (NISP = 53 and MNI = 9). Marine fauna had great relevance as a food source (79.63% of biomass) and as a raw material for artifact manufacturing (65.35% of the artifacts were made from their bones), indicating that marine tetrapods were a relevant resource for sambaqui builders. Data from the sambaquis of southern Brazil were complemented by literature data available on tetrapod fauna inventories on the sambaquis of the Southeast and South regions of the country. The inventory was analysed in terms of absolute and relative taxonomic richness and absolute and relative frequencies of occurrence. The list contains data on 89 sambaquis and a total of 188 taxa, 96 of which are at species level (51.06%): 55 from Mammalia (57.29%), 33 from Aves (34.38%), 7 from Reptilia (7.29%), and one from Amphibia (1.04%). Cuniculus paca (Linnaeus, 1766) and Tapirus terrestris (Linnaeus, 1758) had the highest frequencies of occurrence. The inventory is the most complete comprehensive checklist of sambaquis’ tetrapod fauna and may help with the preservation and management of natural areas and species in a long-term perspective. This is the first doctoral dissertation on sambaquis fauna focused on tetrapods, and here we present information that contributes to our knowledge not only about the culture of the sambaqui builders but also about past biodiversity.